Capacidade de investimento do governo do Estado do Ceará de 2002 - 2012: um quadro comparativo em relação aos demais Estados da Federação - Gomes, Rafael Sampaio (2016)
This dissertation aims to evaluate the investment, and more specifically, the investment capacity of the Government of the State of Ceará, whether it is approached from the use of own resources or from operations with third parties, covering the period from 2002 to 2012 In order to achieve this objective, however, the work begins with a historical descriptive approach to Public Finance in Brazil, bringing to light a series of internal and external events that have influenced the national and state public finances and finances. Subsequently, the analysis focuses on the State of Ceará, seeking to synthesize the evolutionary profile of the public finances of the State and other federal entities, comparing them, using data extracted from the National Treasury Department (STN) to calculate the debt of the State. state. Then, based on the methodology used by the Foundation of Economic Research (FIPE) of the University of São Paulo in partnership with the Paulista Company of Metropolitan Planning (EMPLASA), the analysis of the evolution of investment and investment capacity, or investment potential, by constructing investment capacity indexes with own resources, as well as originating from operations with third parties, aiming to compare the state of Ceará with the other states of Brazil. Brazil. Finally, it is sought to evaluate the results of the evolution of the capacity indices obtained, in an attempt to understand at what stage of evolution the state of Ceará is in relation to such indicators.